2016
DOI: 10.1002/slct.201600843
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Spectroscopy of Green to Yellow Fluorescent Divinylbipyrroles

Abstract: Green and yellow luminescent 4,4′‐dimethyl‐5,5′‐divinyl‐2,2′‐bipyrrole derivatives bearing ester and amide were synthesized from blue luminescent 5,5′‐diformyl‐4,4′‐dimethyl‐2,2′‐bipyrrole and diethyl malonate, 2,2‐dimethyl‐1,3‐dioxane‐4,6‐dione, 1,3‐dimethylbarbituric acid, and 1,3‐dihexylbarbituric acid under Knoevenagel condensation conditions. All the synthesized products clearly showed a red‐shifted π–π* transition absorption band in the visible region compared with the starting bipyrrole. Single‐crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…NMR spectroscopy supported that synthesized divinylbipyrroles derivative ( 2 – 4 ) have good solubility in chloroform. Although 13 C NMR spectrum of the previously reported 1,3-dimethylbarbituric acid adduct, 4Me could not be obtained because of the poor solubility [ 22 ], its analog, 4 , afforded clear 13 C NMR spectrum at similar experimental condition. The 1 H NMR spectral studies revealed that compounds 3 and 4 have hydrogen bonding between NH and CO.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…NMR spectroscopy supported that synthesized divinylbipyrroles derivative ( 2 – 4 ) have good solubility in chloroform. Although 13 C NMR spectrum of the previously reported 1,3-dimethylbarbituric acid adduct, 4Me could not be obtained because of the poor solubility [ 22 ], its analog, 4 , afforded clear 13 C NMR spectrum at similar experimental condition. The 1 H NMR spectral studies revealed that compounds 3 and 4 have hydrogen bonding between NH and CO.…”
Section: Resultsmentioning
confidence: 95%
“…Herein we report synthesis of novel π-extended bipyrrole derivatives 2 – 4 ( Figure 1 B) using activated methylene compounds by means of aldol condensation reaction ( Scheme 1 ), study their photophysical properties and utilize time-dependent density functional theory (TD-DFT) calculations to rationalize the desirable bathochromic shifts observed experimentally. It was found that the introduction of four ethyl groups on the bipyrrole 3 and 3′-positions ( Figure 1 A) resulted in good solubility compared with the previously reported 3,3′-free derivatives [ 22 ]. The improvement of the solubility enabled us to obtain single crystals of 3, and 4, suitable for X-ray diffraction analysis.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations